Synthesis of a novel affinity gel for the purification of carbonic anhydrases. (17th June 2014) - Bozdag, Murat; Isik, Semra; Beyaztas, Serap; Arslan, Oktay; Supuran, Claudiu T.
Abstract: A new affinity gel was synthesized for the purification of carbonic anhydrase (CA, EC 4.2.1.1) isozymes from erythrocytes. The gel was prepared on a Sepharose 4B matrix on which a spacer arm based on ethylenediamine was covalently attached via CNBr activation, followed by reaction with the CA inhibitor 4-isothiocyanato-benzenesulfonamide. The derivatized gel incorporated thioureido-benzenesulfonamide moieties as CA ligand. The binding capacity of the new affinity gel was determined at different temperatures, pH values, ionic strengths and elution buffers. The maximum binding of various CAs was achieved at 25 °C with pH 8.5 and ionic strength around 0.4. The overall purifications for human (h) hCA I and hCA II were 672- and 580-fold, and with 62 and 43% yields, respectively. SDS–polyacrylamide gel electrophoresis showed single bands for each purified isozymes, corresponding to a molecular weight of approx. 29 kDa. This is an easily obtainable, efficient and robust affinity gel, useful for the purification of many other α-CAs.